2017
DOI: 10.1080/10538720.2017.1365671
|View full text |Cite
|
Sign up to set email alerts
|

Access to the labour market for gays and lesbians: Research review

Abstract: This article reviews findings of scientific studies looking into the bias that gay men and lesbians face when accessing the labor market. Studies in this topic were scarce before year 2000, but a considerable body of literature appeared in the Western countries in the recent years. When summed up, the findings provide robust evidence that lesbians and gay men face negative bias when accessing employment. The magnitude of the bias varies considerably across contexts. Different labor market outcomes of gay men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 72 publications
(161 reference statements)
2
20
0
3
Order By: Relevance
“…For gays, this is in line with previous research which showed that homosexuality forms a barrier in their access to employment (Fric 2017). However, the literature is inconclusive for lesbians, providing some evidence that-despite being discriminated in accessing employment-lesbians are more probable to be employed compared to heterosexual women (Fric 2017). My findings suggest that workplace discrimination has qualitatively the same impact on lesbians as it has on gays when it comes to the link with unemployment.…”
Section: Being Unemployedsupporting
confidence: 88%
See 4 more Smart Citations
“…For gays, this is in line with previous research which showed that homosexuality forms a barrier in their access to employment (Fric 2017). However, the literature is inconclusive for lesbians, providing some evidence that-despite being discriminated in accessing employment-lesbians are more probable to be employed compared to heterosexual women (Fric 2017). My findings suggest that workplace discrimination has qualitatively the same impact on lesbians as it has on gays when it comes to the link with unemployment.…”
Section: Being Unemployedsupporting
confidence: 88%
“…The relationship between perceived discrimination and being unemployed is positive and significant for both gays and lesbians. For gays, this is in line with previous research which showed that homosexuality forms a barrier in their access to employment (Fric 2017). However, the literature is inconclusive for lesbians, providing some evidence that-despite being discriminated in accessing employment-lesbians are more probable to be employed compared to heterosexual women (Fric 2017).…”
Section: Being Unemployedsupporting
confidence: 87%
See 3 more Smart Citations